MGMT promoter methylation testing to predict overall survival in people with glioblastoma treated with temozolomide: a comprehensive meta-analysis based on a Cochrane Systematic Review. Issue 9 (30th April 2021) - Brandner, Sebastian; McAleenan, Alexandra; Kelly, Claire; Spiga, Francesca; Cheng, Hung-Yuan; Dawson, Sarah; Schmidt, Lena; Faulkner, Claire L; Wragg, Christopher; Jefferies, Sarah; Higgins, Julian P T; Kurian, Kathreena M
Abstract: Background: The DNA repair protein O 6 -methylguanine-DNA methyltransferase ( MGMT ) causes resistance of tumor cells to alkylating agents. It is a predictive biomarker in high-grade gliomas treated with temozolomide, however, there is no consensus on which test method, methylation sites, and cutoff values to use. Methods: We performed a Cochrane Review to examine studies using different techniques to measure MGMT and predict survival in glioblastoma patients treated with temozolomide. Eligible longitudinal studies included (i) adults with glioblastoma treated with temozolomide with or without radiotherapy, or surgery; (ii) where MGMT status was determined in tumor tissue, and assessed by 1 or more technique; and (iii) where overall survival was an outcome parameter, with sufficient information to estimate hazard ratios (HRs). Two or more methods were compared in 32 independent cohorts with 3474 patients. Results: Methylation-specific PCR (MSP) and pyrosequencing (PSQ) techniques were more prognostic than immunohistochemistry for MGMT protein, and PSQ is a slightly better predictor than MSP. Conclusions: We cannot draw strong conclusions about use of frozen tissue vs formalin-fixed paraffin-embedded in MSP and PSQ. Also, our meta-analysis does not provide strong evidence about the best CpG sites or threshold. MSP has been studied mainly for CpG sites 76-80 and 84-87 and PSQ at CpG sites ranging from 72 to 95. A cutoff threshold of 9% for CpG sites 74-78 performed better than higher thresholds of 28% or 29% in 2 of the 3 good-quality studies. About 190 studies were identified presenting HRs from survival analysis in patients in which MGMT methylation was measured by 1 technique only.